Keynote Address: The Inviolability and Inalienability of Women's Rights - Davide, Jr., Hilario G. (Review of Women's Studies, 2003)
Speech delivered during the book launching of Gender Sensitivity in the Court System on 29 July 2002 at the Manila Hotel.